Metal-induced shifts in benthic macroinvertebrate community composition in andean high altitude streams - Loayza-Muro, RA (2010)
This work was funded by the Consejo Nacional de Ciencia Tecnologia e Innovacion Tecnologica del Peru (Concytec Contract 193 2006)